PENERAPAN SISTEM INFORMASI BERBASIS WEBSITE DI BANARAN KELURAHAN PASIR KIDUL KECAMATAN PURWOKERTO BARAT - Cahyaningsih, Dwi; Rokhayati, Hijroh; Ulfah, Permata; Purwati, Atiek Sri (Jurnal Pengabdian Bisnis dan Akuntansi, 2024)
Banaran is a small area in Pasir Kidul Village, West Purwokerto, Banyumas. Banaran as a typical Banyumas Bandol crafts center is in danger of losing its distinctive characteristics. This makes information related to Bandol Banaran crafts increasingly difficult to find even in the Bandol Banaran crafts center. The website is present as a solution to become an information center for Bandol Banaran crafts. The presence of the Website allows Bandol Banaran crafts to be reached by a wider community. The website provides complete information related to the history of Bandol Banaran crafts, Bandol products, Bandol craft preservation communities, information on Bandol craft preservation activities, as well as product order contact information that can be accessed by the wider community easily and quickly. Information data was obtained through in-depth interview techniques with local craftsmen and cultural experts. The beauty and uniqueness of Bandol crafts are displayed online so that the website can be an information center as well as a promotional tool for Bandol Banaran craft MSMEs. This is expected to help restore the glory of Banaran Bandol crafts and improve its preservation.